Supply chain quality and its managerial challenges: Insights from Ukrainian agri-food business - Jon Hanf; Taras Gagalyuk (Journal for East European Management Studies, 2009)
This article analyses the effect of the East-European business environment on quality management as a means of operationalising chain management strategies. The particular focus on the Ukrainian agri-food business in combination with fifteen in-depth expert interviews reveals the infancy of chain (quality) management in transition economies. General mechanisms of chain management are primarily installed by foreign enterprises acting as focal companies in their supply chain networks. At the same time, progress in operationalisation of chain management (including quality management) is still hampered, mainly due to infrastructural and institutional conditions. – – In diesem Artikel wird der Einfluss wirtschaftlichen Rahmenbedingungen Osteuropas auf das Qualitätsmanagement (QM) analysiert. Hierbei wird QM als Operationalisierung von Chain Management Strategien verstanden. Der Fokus auf das ukrainischen Agribusiness kombiniert mit fünfzehn Tiefeninterviews lassen erkennen, dass die Entwicklung des Chain (Quality) Managements in den Transformationsländern sich erst in der Anfangsphase befindet. Es konnte gezeigt werden, dass im Allgemeinen die Mechanismen des Chain Managements von ausländischen Investoren, die als fokale Unternehmen in ihren Supply Chain Netzwerken agieren, eingeführt werden. Dabei wird der Fortschritt der Operationalisierung von Chain Management (inkl. Qualitätsmanagement) hauptsächlich durch die ungünstigen infrastrukturellen und institutionellen Rahmenbedingungen behindert.
Keywords: 650; Ukraine; agri-food business; supply chain networks; chain quality management